The Development of Instructional Process Based on Constructivism Theory and Cooperative Learning Approach to Enhance the Creative Collaboration Skill - Boonnakkaew, Kittitat; Lomas, Nattasak; Rungjaroen, Nawiya; Poldech, Puripat; Rodprayoon, Wongsakorn; Thanthong, Sutthiporn (SSRU Academic Journal of Education, 2021)
The aims of this research were 1) to develop the instructional process based on the constructivism theory and cooperative learning approach to enhance the creative collaboration skill and 2) to study the effectiveness of the instructional process which was developed. The target group was 23 grade 7 students of Debsirin Nonthaburi School. The research tools were the quality checking form of the instructional process, unit plans, and the assessment form of the creative collaboration skill. The data were analyzed by the applications of mean (x) and standard deviation (S.D.). The results of this research were 1) there are four steps of the instructional process named ICPE; introducing the issue, co-operating with creativity, presenting, and exchanging knowledge. And 2) after using the ICPE instructional process, the creative collaboration skill of the target group was at a medium level ( = 3.47 S.D.=0.88)